A PRACTICAL MODEL FROM MULTIDIMENSIONAL LAYERING: PERSONAL FINANCE INFORMATION FRAMEWORK USING MOBILE SOFTWARE INTERFACE OPERATIONS (Journal of Information and Communication Technology, 2020)
End user involvement is crucial in improving software development processes. Hence, nowadays user interface (UI) and user experience (UX) are particularly concerned with end user interactions in many software designs as most methodologies have inconsistencies between design and implementation. Besides, it is relatively difficult to make changes in complex software and personal finance application is one of the more complex software to design, develop, and adapt. This paper proposes the development of a mobile personal finance application using informative multidimensional layering. We have separated functional data cutting across the relationships of three categories and datasets showing operational semantics of dimensions, and combined layers of three-dimensional information including aspect elements through components. This study is concerned with the corresponsive composition of end user features using visual interfaces. It is illustrated in a Three-layer User Interface Composition Model to transfer and compose layers, functional data, aspect elements, and components to Graphical User Interfaces (GUIs). Therefore, an integrated view of the software system would make the design and implementation consistent to support our framework in a more straightforward manner. There have been a few studies which presented practical models of mobile informative multidimensional layering. This research applied aspect orientation and informative multidimensional layering to present a better features model for mobile personal finance application. We deliver a practical framework in the application in all four phases of analysis, design, implementation, and evaluation. In addressing the gap, this research proposes a clearer operation of three-dimensional models, functional data, and aspect elements that cut across through informative multidimensional layering.